Whole-genome identification of LdELF4s and analysis of their expression response to diurnal temperature variations in Lilium davidii var. willmottiae (E. H. Wilson) raffill - Ma, Xiaohui; Li, Ying; Guo, Xudong; Meng, Lingyu; Wang, Yinquan; Su, Junji; Jin, Ling (Frontiers in Plant Science, 2026)
IntroductionLanzhou lily (Lilium davidii var. willmottiae), a medicinal and edible plant endemic to China, synthesizes bioactive compounds regulated by diurnal temperature variations (DIFs). ELF4 family genes, key regulators coordinating endogenous rhythms with external changes, are unexplored in this species.MethodsWe analyzed nuclear–cytoplasmic phylogeny across 11 species and identified ELF4 homologs. Phylogenetic, collinearity, cis-element, and expression pattern analyses were conducted for Lanzhou lily ELF4s (LdELF4s). qRT–PCR assessed LdELF4 expression under different DIFs (20/20°C, 25/10°C, 20/5°C day/night), and corresponding phenotypes were evaluated.ResultsCytonuclear discordance was observed within Lilium. 62 ELF4 homologs were identified and classified into four subfamilies. Six LdELF4s were located on chromosomes LG01, LG08, LG09, LG12, showing structural variation compared to Lilium sargentiae. LdELF4.1, LdELF4.3, and LdELF4.6 were significantly upregulated at 25/10°C on day 14, while LdELF4.4 and LdELF4.5 were downregulated at 20/5°C. LdELF4.6 showed highest sensitivity. Phenotypically, 25/10°C and 20/5°C treatments delayed flowering by 12.5 and 7.8 days, respectively. The 25/10°C treatment increased stem diameter but reduced flower bud number.Discussion/ConclusionLdELF4.6 is a core candidate gene regulating DIF response in Lanzhou lily, with 25/10°C potentially optimal for bulb development. This study provides genetic resources for breeding climate-adaptive lilies.